Meningkatkan Minat Belajar Siswa Melalui Metode PBL Berbantuan Media Powerpoint untuk Pelajaran PAK dengan Materi Sengsara dan Wafat Yesus Kelas 8 di SMP N 11 Putussibau - Agustinus Lesing; Mawarni Gea; Agustinus Mulyono (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to improve students' learning interest through the application of Problem Based Learning (PBL) aided by PowerPoint in the subject of Catholic Religious Education (PAK) with the topic of Jesus' Passion and Death for 8th-grade students at SMP N 11 Putussibau. The background of this research is the low student interest and understanding of the material. This research uses Classroom Action Research (CAR) conducted in two cycles, where each cycle consists of planning, implementation, observation, and reflection stages. The results show that the PBL method with PowerPoint media can enhance students' interest, understanding, and skills. In cycle I, the observation results showed that students' learning interest was still in the sufficient category, but significantly increased in cycle II after improvements were made. The average cognitive score of students increased from 78 in cycle I to 87 in cycle II, while affective and psychomotor scores also showed significant improvements. This improvement is also evident in the Pancasila Student Profile (P3) dimension, especially in the aspect of Faith in God Almighty and Noble Morality. This, the application of the PBL method with PowerPoint media proved to be effective in improving the quality of learning and students' interest in the Passion and Death of Jesus topic.